Relating fitness to long‐term environmental variations in natura - Pascal Milesi; Thomas Lenormand; Christophe Lagneau; Mylène Weill; Pierrick Labbé (Molecular Ecology, 2016)
Quantifying links between ecological processes and adaptation dynamics in natura remains a crucial challenge. Many studies have documented the strength, form and direction of selection, and its variations in space and time, but only a few managed to link these variations to their proximal causes. This step is, however, crucial, if we are to understand how the variation in selective pressure affects adaptive allele dynamics in natural settings. We used data from a long‐term survey (about 30 years) monitoring the adaptation to insecticides of Culex pipiens mosquitoes in Montpellier area (France), focusing on three resistance alleles of the Ester locus. We used a population genetics model taking temporal and spatial variations in selective pressure into account, to assess the quantitative relationships between variations in the proximal agent of selection (amounts of insecticide sprayed) and the fitness of resistance alleles. The response to variations in selective pressure was fast, and the alleles displayed different fitness‐to‐environment relationships: the analyses revealed that even slight changes in insecticide doses could induce changes in the strength and direction of selection, thus changing the fitness ranking of the adaptive alleles. They also revealed that selective pressures other than the insecticides used for mosquito control affected the resistance allele dynamics. These fitness‐to‐environment relationships, fast responses and continuous evolution limit our ability to predict the outcome of adaptive allele dynamics in a changing environment, but they clearly contribute to the maintenance of polymorphism in natural populations. Our study also emphasizes the necessity of long‐term surveys in evolutionary ecology.